2012
DOI: 10.1111/epi.12010
|View full text |Cite
|
Sign up to set email alerts
|

Posthemispherectomy hydrocephalus: Results of a comprehensive, multiinstitutional review

Abstract: SUMMARY Purpose Hemispherectomy surgery for medically intractable epilepsy is known to cause hydrocephalus in a subset of patients. Existing data regarding the incidence of, and risk factors for developing, post-hemispherectomy hydrocephalus has been limited by the relatively small number of cases performed by any single center. Our goal was to better understand this phenomenon and to identify risk factors that may predispose patients to developing hydrocephalus after hemispherectomy surgery. Methods Fiftee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
78
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 46 publications
(48 reference statements)
8
78
0
2
Order By: Relevance
“…The blood supply to the choroid plexus was not interrupted during the operation, and use of large volumes of hemostatic agents was discouraged when using our hemispherectomy technique. 15 Other components of the perioperative protocol were designed to reduce infections, as previously described. 17 Antibiotic agents (cefazolin or, for allergic patients, clindamycin or vancomycin) were administered intravenously prior to skin incision and were continued postoperatively as noted above.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The blood supply to the choroid plexus was not interrupted during the operation, and use of large volumes of hemostatic agents was discouraged when using our hemispherectomy technique. 15 Other components of the perioperative protocol were designed to reduce infections, as previously described. 17 Antibiotic agents (cefazolin or, for allergic patients, clindamycin or vancomycin) were administered intravenously prior to skin incision and were continued postoperatively as noted above.…”
Section: Study Populationmentioning
confidence: 99%
“…8,13,16,20 Previous studies, including a recent multicenter collaborative project involving different hemispherectomy techniques, have identified type of procedure and previous operations as factors associated with developing posthemispherectomy hydrocephalus. 6,14,15 However, these reports were unable to clearly identify possible links with clinical variables that might suggest mechanisms for developing hydrocephalus after a particular hemispherectomy procedure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that osmotic gradients play a significant part in the regulation of brain water and CSF volume (Hochwald et al, 1974;Wald et al, 1976;Orešković et al, 2002;Maraković et al, 2010;Jurjević et al, 2012). Because of this, it has been presumed that without significant obstruction or stenosis of the CSF system, all pathological processes in which an increase of CSF osmolarity (the osmotic load of CSF) takes place should lead to an increase in CSF volume, and consequently should cause hydrocephalus (Krishnamurthy et al, 2009;Orešković and Klarica 2010; what speaks in favor the most recent multiinstitutional studies of hydrocephalus as a consequence of hemispherectomy surgery for medically intractable epilepsy treatment (Lew et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, they are considered palliative as they may reduce seizure frequency or severity, but do not stop seizure activity (19). A previous study observed that hemispheric and posterior quadrantic disconnection achieved the same rates of seizure control as epileptogenic focus resection in patients with intractable epilepsy (20). Disconnection is achieved by surgical incision to achieve isolation of the epileptogenic foci (21).…”
Section: A B C Dmentioning
confidence: 99%